Advances in nutritional interventions for coronary heart disease patients from the perspective of the gut-heart axis - Gao, Jing; Zhang, Mingjing; Zhang, Gaoning; Zhang, Dingzheng; Zhou, Mo; Zhao, Lijing; Du, Yanwei (Frontiers in Nutrition, 2025)
Coronary heart disease (CHD) is the most common type of cardiovascular disease (CVD) and poses a heavy economic burden worldwide due to its persistently high incidence and mortality rates. In recent years, the pathogenesis of CHD is well-understood, and the “gut-heart axis” theory reveals that the gut microbiota mediated dietary components enter the cardiovascular system via mechanisms including immune metabolism, epigenetics (regulation), and microbial metabolism, which can promote the formation and development of atherosclerosis. This theory identifies the gut microbiota as a promising therapeutic target for CHD intervention. The gut microbiota is highly plastic and closely related to dietary habits. Appropriate nutritional management can achieve the purpose of preventing and treating CHD. From the perspective of the “gut-heart axis,” this review integrates previous research results and current research progress on the gut microbiota in CHD, summarizes the gut microbiota and related pathogenesis in CHD patients, discusses the interrelationship between CHD, nutritional management, and gut microbiota, and explores the existing problems and recent advances in nutritional management of CHD patients, which provides reference ideas for possible therapeutic strategies and precision nutrition support in CHD.